Karakteristik Morfologi Lichen Corticolous Di Kawasan Hutan Sekipan Desa Kalisoro Tawangmangu Karanganyar Provinsi Jawa Tengah - Dekawati, Hermin Sintia; , Ibu Efri Roziaty, S.Si, M.Si (2017)
Research of lichen morphological characteristics corticolous Forest Zone Sekipan Kalisoro Tawangmangu village Karanganyar Central Java province in April 2017. This study aims to determine the morphology of lichen that grows in the region corticolous Sekipan Forest Village Kalisoro Tawangmangu Karanganyar, Central Java province. This study used quantitative descriptive exploratory techniques. The sampling method using purposive sampling. Results corticolous lichen identification, there are 9 species of lichencorticolous Usnea dasaea, Usnea hirta, Usnea subfloridana, Usnea flammea. Usnea subscrabosa, Usnea rubicunda. Usnea sp, Usnea glabrata, and Usnea longissima. Lichen gained entry in Parmeliaceae familiaa. Distribution of lichen colonies corticolous at an altitude of 1300 meters above sea level as much as 22 colonies, an altitude of 1400 meters above sea level as much as 42 colonies and at an altitude of 1500 meters above sea level as much as 172 colonies. Morphology lichen thallus corticolous have type fruticose, with a cylindrical shape and resembles a shrub with a variety of colors and different sizes.